1982
DOI: 10.1038/bjc.1982.241
|View full text |Cite
|
Sign up to set email alerts
|

Studies of lectin binding to normal and neoplastic lymphoid tissues. I. Normal nodes and Hodgkin's disease

Abstract: Lectins are proteins which have the ability to interact specifically with carbohydrate residues of glycoproteins and other glycoconjugates. The staining patterns of 10 fluorescein conjugated lectins (F-Con A, F-LCA, F-RCA, F-WGA, F-PHA, F-PWM, F-LTA, F-SBA, F-PNA, F-DB) and a protease inhibitor (F-LA) have been studied in histological sections of 11 normal or reactive lymph nodes and 6 nodes and one skin biopsy involved by Hodgkin's disease. On the basis of the patterns of lectin binding, and current knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

1982
1982
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…Unlike a recent study (Bramwell et al, 1982) which reported predominantly nuclear binding of PNL, the distribution of staining, in this study, was limited entirely to the cell membrane and/or cytoplasm. In reactive lymph nodes PNL is bound in germinal centres by B lymphoid and reticular cells bearing the terminal carbohydrate residue, galactose-N-acetyl glucosamine (Rose et al, 1981).…”
Section: Recording Of Resultscontrasting
confidence: 47%
“…Unlike a recent study (Bramwell et al, 1982) which reported predominantly nuclear binding of PNL, the distribution of staining, in this study, was limited entirely to the cell membrane and/or cytoplasm. In reactive lymph nodes PNL is bound in germinal centres by B lymphoid and reticular cells bearing the terminal carbohydrate residue, galactose-N-acetyl glucosamine (Rose et al, 1981).…”
Section: Recording Of Resultscontrasting
confidence: 47%
“…20 The utility oflectins (SBA, PNA, and ConA) as probes for identifying mononuclear phagocytes and their malignant derivatives has been investigated previously. 4,13,32 In addition to these lectins, binding with WGA was demonstrated in the Golden Retriever. Detection of lectin receptors in malignant analogs of histiocytes appears to be independent of the degree of differentiation of tumor cells; this independence may assist in the identification of tumors with an intermediate degree of differentiation where markers such as lysozyme may be absent.…”
Section: Discussionmentioning
confidence: 99%
“…Lectin 8taining procedure.-The lectins used and details of the technique are described in the previous paper (Bramwell et al, 1982).…”
Section: Methodsmentioning
confidence: 99%
“…Lymphoid tis8ues.-Lymph nodes were obtained from 22 patients who underwent biopsy for diagnostic or staging purposes and processed as previously described (Bramwell et al, 1982).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation